Phase Content and Flow Measurement of Bubble Flow based on New Experimental Pipeline - L. Fang; S. Wang; S. Li; Y. Faraj; J. Tian; X. Li (Journal of Applied Fluid Mechanics, 2020)
By combining near infrared spectroscopy and differential pressure meter to measure flow rate and phase volume fraction, a new structure of the near infrared system located in the position of the Venturi tube of long throat was proposed. The flow rate and volume fraction of the bubble flow were measured in a vertical experimental line. In terms of volumetric content measurement, based on typical flow characteristics, a void age model was established and experimentally verified. In terms of flow measurement, the classical measurement model is compared, and the uniform flow model is selected as the flow measurement model and corrected. The results show that the measurement error under the bubbly flow condition of the liquid volume fraction and the gas volume fraction was within ±0.52% and ±10%, respectively. The relative error of total flow measurement was within ±1.01%.